2016
DOI: 10.3892/mmr.2016.5949
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyproline-containing collagen peptide derived from the skin of the Alaska pollack inhibits HIV-1 infection

Abstract: The human immunodeficiency virus (HIV) is a lentivirus that results in acquired immunodeficiency syndrome (AIDS). HIV treatment involving chemical therapeutic agents has improved the quality of life of HIV/AIDS patients. The present study demonstrates that a hydroxyproline-containing marine collagen peptide (APHCP) derived from Alaska pollack inhibits HIV-1 infection in the MT-4 human T cell-line. APHCP inhibited HIV-1IIIB-induced cell lysis, syncytia formation, reverse transcriptase activity and viral p24 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Additionally, collagen peptides are key ingredients in nutricosmetic products and supplementary health food because they can increase skin hydration and improve facial skin conditions (Inoue et al 2016). In pharmaceutical applications, a hydroxyprolinecontaining marine collagen peptide from Alaska pollack inhibits human immunodeficiency virus (HIV-1) infection (Jang and Park 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, collagen peptides are key ingredients in nutricosmetic products and supplementary health food because they can increase skin hydration and improve facial skin conditions (Inoue et al 2016). In pharmaceutical applications, a hydroxyprolinecontaining marine collagen peptide from Alaska pollack inhibits human immunodeficiency virus (HIV-1) infection (Jang and Park 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These are small peptides rich in hydroxyproline residues that exhibit anti‐HIV‐1 activity. Jang et al . reported the anti‐HIV‐1 activity of their novel antiretroviral peptide with unique underlying mechanisms of action.…”
Section: Collagen Peptidesmentioning
confidence: 99%
“…Marine sponges are not the sole source of bioactive proteins. For example, Jang et al reported about a new small hydroxyproline-rich peptide from Alaska Pollack collagen (APHCP, 21 , Figure 8) that exhibits a unique antiviral activity [94]. This peptide is a Gly-Pro-Hyp-Gly-Pro-Hyp-Gly-Pro-Hyp-Gly peptide, and the authors showed that the most important part of a peptide for anti-HIV activity is the hydroxyl group at hydroxyproline, whereas a peptide with only prolines does not exhibit antiviral activity.…”
Section: Marine Compounds In the Treatment Of Hiv/aidsmentioning
confidence: 99%